Нужна помощь в решении номера 6(б)

0 голосов
26 просмотров

Нужна помощь в решении номера 6(б)


image

Алгебра (53 баллов) | 26 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\sqrt{( \sqrt{9-6 \sqrt{2} } + \sqrt{9+6 \sqrt{2} )^2} } = \sqrt{9-6 \sqrt{2} +2 \sqrt{81-72} +9+6 \sqrt{2} } =\sqrt{18+2*3} = \sqrt{24} =2 \sqrt{6}
0

Выручил, спасибо

0 голосов
t=\sqrt{9-6\sqrt2}+\sqrt{9+6\sqrt2}\\t^2=(\sqrt{9-6\sqrt2}+\sqrt{9+6\sqrt2})^2=\\=9-6\sqrt2+2\sqrt{(9-6\sqrt2)(9+6\sqrt2)}+9+6\sqrt2=\\=18+2\sqrt{81-54\sqrt2+54\sqrt2-72}=18+2\sqrt{9}=24\\t=\sqrt{24}=2\sqrt{6}
Ответ: иррациональное.
(7.7k баллов)
0

Спасибо